



 
Hi, I am going to illustrate how to solve this using the example
The first step is to multiply through the parentheses on both sides. On the left
Using he same procedure on the right and collecting like terms I get
To collect all the terms involving v on the left side add 6v to each side
Finally add 8 to each side
Thus v = 1. You should now substitute v = 1 in the original expression 3v  4(2 + v) = 3(2v + 1) to check if v = 1 is the correct solution. Now try v4(4v) = 2(2v1). Penny  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 